Neuroendocrine carcinoma of the breast: a case report and review of the literature - Eyvaz, Kemal; Alikanoğlu, Arsenal Sezgin; Hamamcı Özak, Evrim; Kazan, Murat Kazim; Çakır, Tuğrul (The European Research Journal, 2022)
Neuroendocrine carcinoma (NEC) is a very rare condition among other types of invasive cancer of breast. Whole-body screening should be performed in order to detect any metastatic or primary disease localization. A 58-year-old patient admitted to hospital with palpable mass on the right retro areolar region and with bloody nipple discharge. Due to axillary positivity with a diagnosis of neuroendocrine carcinoma neoadjuvant chemotherapy was performed. The pathological stage was reported T2N2 with a 2 cm tumor and 5 of 11 lymph node positivity after modified radical mastectomy following neoadjuvant therapy. Tumor cells were stained with positive for neuroendocrine markers. She received adjuvant hormonal treatment with aromatase inhibitors and on regular follow-up with a free of disease to date. The neuroendocrine tumor of the breast is a diagnosis of exclusion. Primary or metastasis distinction is compulsory for the planning of appropriate treatment. There is still a debate on how neuroendocrine differentiation affects the clinical outcome.